Art and Obscenity. - Mey, Kerstin (Art and Series., 2006)
Explicit material is more widely available in the internet age than ever before, yet the concept of 'obscenity' remains as difficult to pin down as it is to approach without bias: notions of what is 'obscene' shift with societies' shifting mores, and our responses to explicit or disturbing material can be highly subjective. In this intelligent and sensitive book, Kerstin Mey grapples with the work of twentieth-century artists practising at the edges of acceptability, from Hans Bellmer through to Nobuyoshi Araki, from Robert Mapplethorpe to Annie Sprinkle, and from Hermann Nitsch to Paul McCart.